Respuesta :

Answer:

Step-by-step explanation:

[tex]\frac{4}{5+6}=\frac{4}{11}\\\\3+\frac{4}{5+6}=3+\frac{4}{11}\\\\=\frac{3*11}{1*11}+\frac{4}{11}\\\\=\frac{33+4}{11}\\\\=\frac{37}{11}\\\\\\\frac{2}{3+\frac{4}{5+6}}=\frac{2}{\frac{37}{11}}\\\\=2*\frac{11}{37}\\\\=\frac{22}{37}\\\\\\\\1+\frac{2}{3+\frac{4}{5+6}}=1+\frac{22}{37}\\\\=\frac{37}{37}+\frac{22}{37}\\\\=\frac{37+22}{37}\\\\=\frac{59}{37}\\\\=1\frac{22}{37}\\[/tex]

Answer

[tex]59/37[/tex]

Explanation

[tex]1+\frac{2}{3+\frac{4}{5+6} }[/tex]

[tex]1+\frac{2}{3+\frac{4}{11} }[/tex]

[tex]1+\frac{2}{\frac{3}{1} +\frac{4}{11} }[/tex]

[tex]1+\frac{2}{\frac{33}{11} +\frac{4}{11} }[/tex]

[tex]1+\frac{2}{\frac{37}{11} } }[/tex]

[tex]1+2 \times \frac {11}{37}[/tex]

[tex]1+\frac{22}{37}[/tex]

[tex]1\frac{22}{37}[/tex]

[tex]\approx 1.594594594594594594594594594594595[/tex]

ACCESS MORE